Performing popular music the art of creating memorable and successful performances - Cashman, David; Garrido, Waldo 1962- (New York, NY Routledge, 2020)
This book explores the fundamentals of popular music performance for students in contemporary music institutions. Drawing on the insights of performance practice research, it discusses the unwritten rules of performances in popular music, what it takes to create a memorable performance, and live popular music as a creative industry. The authors offer a practical overview of topics ranging from rehearsals to stagecraft to what to do when things go wrong. Chapters on promotion, recordings, and the music industry place performance in the context of building a career. Performing Popular Music introduces aspiring musicians to the elements of crafting compelling performances and succeeding in the world of today's popular music"--
includes bibliographical references and index.
Keywords: Music -- Performance; Popular music -- Instruction and study; Popular music -- Vocational guidance